TANTANGAN PEMERATAAN PENDIDIKAN DI WILAYAH 3T INDONESIA - Nisa, Nurul; Yan Dirk Wabiser; Lusia N. Amsad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Equitable education is a constitutional mandate and a development agenda that demands equal access and quality education services throughout Indonesia. However, the Disadvantaged, Frontier, and Outermost (3T) regions still face structural gaps: limited school infrastructure and connectivity, unequal distribution and professional development of teachers, disparities in access to learning technology, and challenges in curriculum relevance to local contexts. This article aims to analyze the challenges of equitable education in the 3T regions in the 2020–2025 period through a semi-systematic literature review. Data sources include accredited national journals (SINTA) and reputable national journals, international articles indexed/standardized by Scopus and international sources, and policy reports from official institutions (UNICEF, OECD, World Bank). The study results show that the post-pandemic digital acceleration opens up opportunities for innovation, but also widens the digital divide without the support of infrastructure, digital literacy, and sustainable affirmative policy design. This article recommends four policy directions: (1) meeting minimum service standards for infrastructure and connectivity, (2) affirming teacher placement and strengthening competencies, (3) strengthening an inclusive digital learning ecosystem, and (4) developing a contextual curriculum based on local needs and learning recovery.